Health status, practices and reported effects of the MT Solar I oil spill on residents and clean up workers in Nueva Valencia, Guimaras - Malecosio, Serafin O. Jr.; Naragdao, Mary Ann A.; Gonzalez, Maria Kristina S.; Ferrer, Alice Joan G. (2009)
This is a cross-sectional study design that compared the self-reported health symptoms among the affected residents living along the coastal barangays affected by M/T Solar 1 oil spill in Nueva Valencia, Guimaras before and after the oil spill. It compared the symptoms between clean up and non-clean up workers of the exposed study population, and described the health status of clean up workers. There were 3,174 individuals interviewed: 2,841 belong to the exposed and 333 to the unexposed group. Of these, 124 oil spill cleanup workers in the exposed group and 37 in the unexposed were selected. The respiratory function, kidney and liver organ functions, hemoglobin and hematocrit levels of these selected clean up workers were analyzed.

Self-reported symptoms among the exposed residents were significantly increased after the oil spill incident after adjusting for the effects of age, sex, alcohol intake and smoking. The odds of developing fever/flu (POR= 6.38, P=0.000), skin blisters (POR= 5.43, P=0.000), stomach ache (POR= 4.9, P=0.000), chest pains (POR=4.88, P=0.000) and watery eyes (POR 4.09, P=0.000) were significantly higher after the oil spill than before the oil spill in the exposed population. Clean up workers were four times more likely to develop sore throat compared with the non-clean up workers in the exposed population (P=0.0000).Clean up workers showed significantly low peak expiratory flow (P=0.000), elevated SGPT (3%), SGOT (2%), Creatinine (20%), Blood Urea Nitrogen (24%), low hemoglobin (14%) and low hematocrit (20%) levels. About three fourth of clean up workers were hired without completing the required medical requirements.

The study recommends long-term monitoring of the health effects of oil spill on the exposed population, particularly clean up workers,.stricter screening procedures and selection of clean up workers, provisions of correct protective equipment, adequate training, and proper monitoring on the use of personal protective equipment in the field.
Keywords: Oil spill management; Oil spills -- Cleanup -- Guimaras